Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species - Wang, Shuxia; Liu, Chen (Zootaxa, 2020)
The densimacularis species group of the genus Promalactis Meyrick, 1908 is proposed based on the forewing patterns. These species are diagnostic by the forewing having three black patches on the costal margin, the gnathos usually with a membranous apical process in the male genitalia, and the ductus bursae with denticles or spines in the female genitalia. Four new species are described: P. costispinata sp. nov., P. trimaculata sp. nov., P. simingshana sp. nov. and P. yongjiana sp. nov. All the 14 described species of the densimacularis-group are listed. Photographs of adults and genitalia of the new species are provided.